Acts of rebellion : the Ward Churchill reader - Churchill, Ward (Routledge, 2003)
What could be more American than Columbus Day? Or the Washington Redskins? For Native Americans, they are bitter reminders that they live in a world where their identity is still fodder for white society. ""The law has always been used as toilet paper by the status quo where American Indians are concerned, "" writes Ward Churchill in Acts of Rebellion, a collection of his most important writings from the past twenty years. Vocal and incisive, Churchill stands at the forefront of American Indian concerns, from land issues to the American Indian Movement, from government repression to the histor.